FACTORS THAT INFLUENCE THE LEVEL OF PROFITABILITY MANAGERIAL IN MEDAN - Sembiring, Seniwati; Damanik, Syafrida; Putra, M. Umar Maya; Maliyah (International Journal of Research -GRANTHAALAYAH, 2020)
The purpose of this study was to determine the effect of the Current Ratio (CR), Debt to Equity Ratio (DER) and Total Assert Turn Over (TATO) on profitability Managerial in Return on Assert (ROA) for the period 2008-2017. The sample of financial statements that were studied for 10 years at PT. Ira Widya Utama as one of the biggest company In Medan. The data used is secondary data. This study analyzes the relationship among them. The statistical method used is multiple linear regression using the classic assumption test first. It indicates that partially the CR has a negative significant effect, DER has a positive and insignificant effect, TATO has a positive and significant effect on ROA. simultaneously, CR, DER and TATO have a positive and significant on ROA.